1983
DOI: 10.1111/j.1365-2125.1983.tb02152.x
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of orally administered amphotericin B lozenges.

Abstract: The systemic absorption of amphotericin B, administered as a 10 mg lozenge, was investigated in 14 patients with malignancies, who received three or four doses daily during chronic administration.The mean plasma amphotericin B concentration, measured 3 h after the morning dose on from 1-20 occasions over a 1-80 day period, ranged among subjects from 46 ± 13 ng/ml (s.d., n = 20) to 136 ± 25 ng/ml (n = 19).Using the previously reported intravenous clearance of the drug, the fraction of the dose absorbed was esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…Commercial amphotericin B oral suspension contains flavorings designed to overcome this problem, although it is reported that some patients find the taste disagreeable. Systemic absorption of orally administered amphotericin is reported to be minimal except after antineoplastic chemotherapy [47, 42,15], and systemic absorption was assessed in the current study. The minimal blood levels of amphotericin B seen in the current trial suggest minimal though measurable uptake of amphotericin B despite limited compliance with use of the rinse.…”
Section: Discussionmentioning
confidence: 99%
“…Commercial amphotericin B oral suspension contains flavorings designed to overcome this problem, although it is reported that some patients find the taste disagreeable. Systemic absorption of orally administered amphotericin is reported to be minimal except after antineoplastic chemotherapy [47, 42,15], and systemic absorption was assessed in the current study. The minimal blood levels of amphotericin B seen in the current trial suggest minimal though measurable uptake of amphotericin B despite limited compliance with use of the rinse.…”
Section: Discussionmentioning
confidence: 99%
“…DAMB therapy is associated with nephrotoxicity, central nervous system and liver damage, and side effects such as nausea and fever (23,34,35). AMB, with its inherent low solubility in water and many organic solvents, shows relatively poor bioavailability (11,12). In order to increase the therapeutic index of AMB and reduce its associated toxicity, new lipid-based formulations have been developed (1,3,33).…”
mentioning
confidence: 99%
“…The estimated absorbed fraction of conventional AmB in human was calculated to be 0.86% after a 2 g oral dose which is not effective 20 . Although the therapeutic levels can be reached by the administration of parenteral formulations, the high cost and the complications of injectable formulations limit their wide use.…”
Section: Discussionmentioning
confidence: 99%